Return to play in elite rugby players after severe knee injuries - Aneurin D. Robyn; Quinette A. Louw; Jochen Baumeister (AOSIS, 2022)
Background: Medical professionals working in an elite sport environment have the challenging task to balance the athlete's readiness to return to the playing field after severe injury with other stakeholders' (coaches, sponsors, teammates) opinions and objectives. Objectives: Our study aimed to evaluate differences in the physical profiles of elite rugby players at return to play (RTP) after a severe knee injury, compared with their pre-injury profiles and matched controls. Method: Before the injury, participants performed four performance tests during their preseason screening. These tests were repeated and compared to baseline once a player was declared fit to play. Results: Significant differences (p ≤ 0.05) were found in the injured players' group who were slower over 10 m speed, in their decision-making time and the total time of the reactive agility tests at RTP, whilst controls were significantly faster over 10 m and 30 m speed tests. The countermovement jump outcomes showed significant improvement in the uninjured participants (p ≤ 0.05). Conclusion: Our study highlights that injured players' running speeds and decision-making times are slower after injury. The uninjured players have a positive outcome to training and match stimulus by improving their running speed and lower body explosive power during the season. Clinical implications: Our study provides insight into the RTP profile of elite rugby players, and a novel finding was the decision-making time deficit. This highlights the importance of cognitive training during injury rehabilitation as athletes make numerous decisions in a pressured and uncontrolled environment during a match. Speed training development is recommended as the athletes were slower after severe knee injury.